2021
DOI: 10.3390/ani12010014
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rearing Conditions on Carcass Traits, Meat Quality and the Compositions of Fatty Acid and Amino Acid of LTL in Heigai Pigs

Abstract: The present study evaluates the influence of captivity and grazing rearing conditions on the carcass traits, meat quality and fatty acid profiles of Heigai pigs. Ten Heigai pigs with market weight were randomly selected from both the indoor feeding farm and outdoor grazing farm groups (FF and GF; five pigs per group) for measuring production performance. The results showed that the shear force of longissimus thoracis et lumborum (LTL) in the GF group tended to increase (p = 0.06), and triglyceride and choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In this study, the pH of the free-range group was significantly higher than that of the other two groups, which is consistent with previous studies, and it was concluded that the pH of meat products from outdoor, slow-growing broilers was higher than that of indoor, slow-growing broilers [ 22 ]. The reason for the high pH in free-range chickens may be related to the relatively low content of muscle glycogen, and the lower lactic acid through the anaerobic pathway when it decomposed [ 23 ]. Of all the sensory characteristics, tenderness is considered to be the most important by consumers, which means meat can be chewed or cut [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the pH of the free-range group was significantly higher than that of the other two groups, which is consistent with previous studies, and it was concluded that the pH of meat products from outdoor, slow-growing broilers was higher than that of indoor, slow-growing broilers [ 22 ]. The reason for the high pH in free-range chickens may be related to the relatively low content of muscle glycogen, and the lower lactic acid through the anaerobic pathway when it decomposed [ 23 ]. Of all the sensory characteristics, tenderness is considered to be the most important by consumers, which means meat can be chewed or cut [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, fatty acid metabolism strongly influences meat quality. Previous studies have found that the fatty acid composition and its metabolism in muscles are important factors influencing overall meat quality and consumer preference ( Ayuso, et al, 2015 ; Albuquerque, et al, 2021 ; Li, et al, 2022a ). Genetic and environmental factors combine to make meat quality a complex trait, and there can be large variations in meat quality within and between animals ( Rehfeldt, et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…[52] have not shown any significant impact of housing condition or production system on meat sensory quality. But, in a study done on Heigai pigs, those grown on grazing farms had a better meat quality and higher nutritional value than those grown on indoor feeding [53]. Since the sample size was small, the results can't be representative.…”
Section: Rearing Systemmentioning
confidence: 95%